Inorganic-based adsorbent materials for the removal of gaseous pollutants - Asim N.; Badiei M.; Torkashvand M.; Alghoul M.A.; Samsudin N.A.; Amin N.; Sopian K. (Springer Science and Business Media Deutschland GmbH, 2023)
Accident prevention; Costs; Energy utilization; Fog; Pollution control; Adsorption technology; Anthropogenic activity; Competitive adsorption; Inorganic adsorbent; Inorganic materials; Low energy consumption; Simple modifications; Various technologies; Gas adsorption; adsorption; environmental fate; human activity; industrial emission; inorganic matter; pollutant removal